New electrostatic phase plate for phase-contrast transmission electron microscopy and its application for wave-function reconstruction - Schultheiß, Katrin; Zach, Joachim; Gamm, Bjoern; Dries, Manuel; Frindt, Nicole; Schröder, Rasmus R.; Gerthsen, Dagmar (Microscopy and microanalysis, 2010)
A promising novel type of electrostatic phase plate for transmission electron microscopy (TEM) is presented. The phase plate consists of a single microcoaxial cable-like rod with its electrode exposed to the undiffracted electrons. The emerging field is used to shift the phase of the undiffracted electrons with respect to diffracted electrons. The design overcomes the drawback of the spatial frequency-blocking ring electrode of the Boersch phase plate. First, experimental phase-contrast images are presented for PbSe and Pt nanoparticles with clearly varying phase contrast, which depends on the applied voltage and resulting phase shift of the unscattered electrons. With the new phase-plate design, we show for the first time the reconstruction of an object wave function based on a series of only three experimental phase-contrast TEM images obtained with an electrostatic phase plate.
Gesehen am 05.07.2023